The route of Yannick Bourseaux - Bourseaux, Y. (Science + Triathlon 2015 World Conference, 2015)
I started triathlon in 1989 when I was 14 after a few years of swimming and running. Quickly, I performed in the discipline. In 1994 I get gold at junior French Championship and in 1995 silver at European. Once I left junior category, I move into long distance national team and then continue my practice while having a professional activity. In 2004, during a training camp, I crashed on my bike. Fortunately, I keep as the only sequel to the fall a partial paralysis of my right arm. This disability didn`t allow me to continue my sport with able body people so I move to disabled sports practice. At that time, paratriathlon wasn`t yet a Paralympic sport. The practice was not well structured and the international field was quite low. In 2005, because I was already practicing cross-country skiing as part of my triathlon fitness training before and because Nordic skiing was Paralympic, I decided to swap my sport career to this discipline. I quickly drag biathlon. Then I found the motivation to push myself again and set myself high level goals. Between 2009 and 2013,1 won a medal at each of the three IPC World Championships I took part and was two times paralympian (Turin 2006 and Vancouver 2010). The Para-Nordic international circuit is done under the aegis of the IPC and not the FIS or the IBU and in France the discipline is managed by the French Disabled Sports Federation (FFH) and not by the French Ski Federation (FFS). In December 2010, IPC decided that paratriathlon will make its debut at Rio 2016 Paralympic Games. In April 2013, the French Triathlon Federation (FFTri) launched its project «Rio 2016 paratriathlon». Seduced by it, I decided not to go to Sochi Games to return to my original sport with the goal of winning a Paralympic medal in Rio. The International Triathlon Union (ITU) is responsible for development and organization of paratriathlon at international level. In France, it is also FFTri and not FFH which develops and organizes paratriathlon. Therefore, there is a real mix between triathletes and paratriathletes. We attend the same training sites, the same race venues and work with the same technical or medical staff. This mix brings a recognition by the valid sphere that I did not know in Nordic skiing. I think this helps to maintain at a high level paratriathlete`s motivation. Finally, two paratriathletes sit on the ITU athlete`s committee with 6 other triathletes to make the voice of paratriathlon in decision-making.